2018
DOI: 10.1021/acs.jpcc.8b05731
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Preparation Procedure of Vanadium-Containing SiBEA Zeolites on Their Catalytic Activity in Propene Epoxidation

Abstract: Two series of V-containing BEA zeolite catalysts, V x SiBEA(I) and V x SiBEA(II), were prepared by a two-step postsynthesis preparation procedure which consists, in the first step, in the dealumination of TEABEA zeolites by a treatment with nitric acid solution to obtain SiBEA zeolites with a Si/Al atomic ratio of 1000 and then, in the second step, in bringing SiBEA into contact with an aqueous NH 4 VO 3 solution with different concentrations at a pH of 2.7. After 3 days, the solids were recuperated from the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…The obtained solids were then dried in air at 353 K for 24 h and labeled V 0.6 SiBeta(II) and V 1.6 SiBeta(II). V 0.1 SiBeta(I), V 0.5 SiBeta(I), V 1.0 SiBeta(I), V 1.4 SiBeta(I), V 0.6 SiBeta(II) and V 1.6 SiBeta(II) samples were all white, suggesting the presence of pseudo-tetrahedral V(V) species, in line with our earlier reports [30,31]. In contrast, V 7.5 SiBeta(I) and V 1.0 SiBeta(II) samples were pale yellow suggesting the presence of not only pseudo-tetrahedral but also pseudo-octahedral V(V) species, either as mononuclear and/or polynuclear V(V) species, in agreement with our earlier reports [30,31].…”
Section: Materials Preparationsupporting
confidence: 91%
See 1 more Smart Citation
“…The obtained solids were then dried in air at 353 K for 24 h and labeled V 0.6 SiBeta(II) and V 1.6 SiBeta(II). V 0.1 SiBeta(I), V 0.5 SiBeta(I), V 1.0 SiBeta(I), V 1.4 SiBeta(I), V 0.6 SiBeta(II) and V 1.6 SiBeta(II) samples were all white, suggesting the presence of pseudo-tetrahedral V(V) species, in line with our earlier reports [30,31]. In contrast, V 7.5 SiBeta(I) and V 1.0 SiBeta(II) samples were pale yellow suggesting the presence of not only pseudo-tetrahedral but also pseudo-octahedral V(V) species, either as mononuclear and/or polynuclear V(V) species, in agreement with our earlier reports [30,31].…”
Section: Materials Preparationsupporting
confidence: 91%
“…SiBeta(I) (Fig.6b, spectra a to d) and calcined V 0.6 SiBeta(II) (Fig.7b, spectrum a) exhibit two bands at 245 and 295 nm. The shift of these DR UV-vis charge-transfer bands to lower wavelengths upon calcination suggests a greater distortion of pseudo-tetrahedral V(V) species in calcined samples than that in as prepared ones, in agreement with earlier work[30][31]. In contrast, two main bands appear at 245 and 275 nm for calcined V 1.0 SiBeta(II) and at 245 and 295 nm for V 1.6 SiBeta(II) (Fig.7b, spectra b and c, respectively) attributed to oxygen-topseudo-tetrahedral V(V) charge transfer transitions, involving oxygen in bridging (V-O-Si) and terminal (V=O) positions, respectively with a shoulder at about 335 nm attributed to oxygen-to-pseudo-octahedral V(V) charge transfer transition.…”
supporting
confidence: 90%
“…Analogous tendency has been reported in literature for V-containing catalysts. 38 Selectivity for acrolein (ACR) was affected neither by the reaction temperature nor by the catalyst structure, being about 10%, and only a slight decrease of ACR selectivity with increasing reaction temperature was observed. According to our earlier ndings, propene oxide and acetone are mostly primary products of propene oxidation, whereas acrolein is formed over nucleophilic forms of oxygen.…”
Section: Catalytic Performance For Propene Epoxidationmentioning
confidence: 99%
“…It is reported that SiBeta support can effectively disperse and stabilize the introduced VOx species due to the existence of vacant T-sites after removing lattice Al atoms [25,26]. The V-loaded SiBeta serving as effective heterogeneous catalysts have been applied in various catalytic reactions, such as methanol oxidation, NO reduction, conversion of carbohydrates into 2,5-diformylfuran and propene epoxidation [27][28][29][30]. Noticeably, it is confirmed that the catalytic performance of VSiBeta catalysts in some reactions depends on the type of VOx species, which is mainly controlled by V loading amount [21,26,31].…”
Section: Introductionmentioning
confidence: 99%